PORTER’S GENERIC COMPETITIVE STRATEGIES, ALLIANCE PARTNERSHIPS AND PERFORMANCE OF MOBILE TELEPHONE NETWORK SERVICE PROVIDERS IN KENYA - MUSYOKA, MARGARET NDUNGE (MksU Press, 2023)
Past studies on the relationship between Porter’s generic strategies and firm performance in the presence of alliance partnerships continue being an unresolved predicament with most studies resulting to diverse outcome. The main objective of this study was to investigate the influence of Porter’s generic competitive strategies and alliance partnerships on performance of mobile telephone network service providers in Kenya.The specific objectives were; to examine the influence of focus strategy on performance of mobile telephone network service providers in Kenya, to explore the influence of cost leadership strategy on performance of mobile telephone network service providers in Kenya, to investigate the influence of differentiation strategy on performance of mobile telephone network service providers in Kenya, to investigate the moderating effect of alliancepartnerships on the relationship between Porter’s competitive strategies and performance of mobile telephone network service providers in Kenya and to establish the joint effect of Porter’s competitive strategies and alliance partnerships on performance of mobile telephone network service providers in Kenya. The study was underpinned by transaction cost theory, ResourceBased View (RBV) theory, syncretic paradigm theory and shareholder value maximization theory. The study pursued a positivism research philosophy and descriptive research design methodology. The target population was all the 66 registered mobile telephone network service providers in Kenya. Primary data was gathered through useof structured questionnaires. Descriptive statistics, correlation and regression modeling was used to aid in data analysis. Descriptive analysis portrayed that the 61 mobile telephone network service providers in Kenya pursued the three Porter’s competitive strategies as follows; 23% (14) of those firms adopted focus strategy, 18% (11) on cost leadership strategyand 39.3% (24) adopted the differentiation strategy. Another 8.2% (5) pursued either two of the three strategies and another 9.8% (6) opted for the three strategies. It was only 1.6% (1) ofthe 61 which did not adopt any of the Porters’ strategies in their operations. On the other hand,inferential statistics revealed that focus strategy had significant influence on firm performancewith β=82.3 %(P=.000); cost leadership strategy had significant straight influence on firm performance with β=76.9%(P=.000). Differentiation strategy had statistically significant influence on firm performance with β=83.2 % (P=.000). Alliance Partnerships in overall portrayed statistically significant moderating effect on the relationship between Porter’sgeneric competitive strategies and firm performance with all F statistics being significant withp=.000 in the three tests undertaken. The joint influence of Porter’s generic competitive strategies, Alliance Partnerships on firm performance was statistically significant with F=20.822(p<.05). In conclusion, alliance partnership was a conditional factor as far as the relationship between Porter’s strategies and firm performance is concerned. The study suggests that organizations should look into the depth in which individual components of Porters’ competitive strategies impact on performance other than concentrating the on the composite dynamics and then go on to consider the most favorable strategies which optimize their business sustainability level so as to have competitive edge in the market. Again, it is important for firms to consider alliance partnerships as a conditional factor rather than a pure predictor of firm performance.